Competing ethical paradigms in forensic psychiatry and forensic psychology: commentary for a special section of legal and criminological psychology - Day, Andrew (Legal and criminological psychology, 2014)
In her paper Gwen Adshead (2013) identifies the principle of respect for justice as the foundation for ethical practice in forensic psychiatry. This commentary discusses how forensic psychologists have approached a key aspect of the justice principle, the ethical imperative to promote the welfare of the individual client. The approaches of the psychiatric and psychological professions are compared and the role of psychologists as allied health professionals working in the forensic setting considered.